ISLAM LIBERAL DALAM BINGKAI MEDIA: ANALISIS FRAMING MAJALAH GATRA DAN SABILI - Farida, Ade Bina (Fakultas Dakwah IAIN Purwokerto, 2011)
The same theme can be interpreted differently and produce different story. Similarly, the preaching of liberal Islam in the media. From the study of text analysis here, with framing analysis model from Gamson and Modigliani, it can be seen the difference and Sabili magazine Gatra in addressing the existence of the JIL (Liberal Islam NetWork) and the attitude of both media to the ideas brought by the liberal Islamic thought. There are many differences that can be seen from the appearance of both news media. In general, Gatra magazine tend to be open to ideas of liberal Islam. Of the sources interviewed, Gatra attempted cover both sides, both from the liberal Islam and Islamic fundamentals. However, itremainsthe largest portion given to supporters of liberal Islam. In terms of writing technique, very few raises Gatra personal opinion joumalistdiredly. Sabili magazine, generally showing harsh criticism on liberal Islam. Sabili, for example, put a liberal Islam as a cult and misleading, a nosy group, or judged as a community that can destroy the faith.